Two-level approximation method for reliability-based design optimisation. (29th November 2005) - Gea, Hae Chang; Oza, Kunjal
In order to model uncertainties and achieve the required reliability, Reliability-Based Design Optimisation (RBDO) has evolved as a dominant design tool. Many methods have been introduced to solve the RBDO problem. However, the computational expense associated with the probabilistic constraint evaluation still limits the applicability of the RBDO to practical engineering problems. In this paper, a Two-Level Approximation method (TLA) is proposed. At the first level, a reduced second order approximation is used for better optimisation solution; at the second level a linear approximation is used for faster reliability assessment. The optimal solution is obtained iteratively. The proposed method is tested on certain numerical examples, and results obtained are compared to evaluate the cost-effectiveness.